The effect of dust grain temperature and dust streaming on electrostatic solitary structures in a non-thermal plasma - Maharaj, S.K.; Pillay, S. R.; Bharuthram, R.; Singh, S. V.; Lakhina, G. S. (My University, 2004)
The influence of dust temperature and dust streaming on dust acoustic solitary waves is investigated in an unmagnetized dusty plasma comprising negatively charged dust, non-thermal ions and Boltzmann electrons. It is found that the conditions which support the coexistence of both compressive and rarefactive solitons is altered by the dust temperature and by dust streaming.
Keywords: Electrostatic solitary waves; Non-Thermal plasma; Dust temperature; Dust streaming; Solitary waves